2015
DOI: 10.1152/jn.00477.2014
|View full text |Cite
|
Sign up to set email alerts
|

Parallax-sensitive remapping of visual space in occipito-parietal alpha-band activity during whole-body motion

Abstract: Gutteling TP, Selen LP, Medendorp WP. Parallax-sensitive remapping of visual space in occipito-parietal alpha-band activity during whole-body motion. J Neurophysiol 113: 1574 -1584, 2015. First published December 10, 2014 doi:10.1152/jn.00477.2014Despite the constantly changing retinal image due to eye, head, and body movements, we are able to maintain a stable representation of the visual environment. Various studies on retinal image shifts caused by saccades have suggested that occipital and parietal areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 60 publications
5
38
1
Order By: Relevance
“…A fixedinterval procedure was used, equally spaced over 9 locations, spanning 8 degrees of visual angle, with a maximum of 12 degrees depending on subject performance. Due to the general underestimation of self-motion in these updating tasks (Clemens et al, 2012;Gutteling et al, 2015) probe locations were shifted towards the fixation point (consistent with an underestimation of motion), but always contained the veridical location.…”
Section: Paradigmmentioning
confidence: 74%
See 3 more Smart Citations
“…A fixedinterval procedure was used, equally spaced over 9 locations, spanning 8 degrees of visual angle, with a maximum of 12 degrees depending on subject performance. Due to the general underestimation of self-motion in these updating tasks (Clemens et al, 2012;Gutteling et al, 2015) probe locations were shifted towards the fixation point (consistent with an underestimation of motion), but always contained the veridical location.…”
Section: Paradigmmentioning
confidence: 74%
“…In Gutteling et al (2015), we showed that alpha band power across occipital-parietal areas switches hemispheres when a target location reverses sides relative to the body midline (which was aligned with gaze) during the motion. More specifically, an increase of power was observed in the hemisphere to which the target representation was remapped.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…In one study, participants received tactile stimulation on the index or little finger of one hand while fixating the same hand's middle finger (Buchholz et al, 2011). While planning a saccade to the tactile location, posterior parietal alpha-band activity was suppressed in the hemisphere opposite to finger location relative to gaze, as it has been reported for visual paradigms as well (Gutteling et al, 2015). In another study, touch to uncrossed and crossed hands also resulted in externally coded parietal alphaband suppression (Schubert et al, 2018).…”
Section: Lateralized Alpha-band Suppression In Response To Tactile Stmentioning
confidence: 88%